Adaptability and Stability Analysis for Selection of Elephantgrass Clones under Grazing. Issue 2 (1st March 2015) - Viana, Bruno L.; de Mello, Alexandre C. L.; de A. Lira, Mário; Guim, Adriana; Dubeux, José C. B.; dos Santos, Mércia V. F.; da Cunha, Márcio V.
ABSTRACT: Adaptability is the capacity of a genotype to respond favorably to changes in the environment, while stability is the capacity to have highly predictable performance in different environmental conditions. In this study, the stability and adaptability of eight Pennisetum spp. clones were assessed. Genotypes analyzed in this research included five dwarf elephantgrass ( Pennisetum purpureum Schumach.) cultivars (Taiwan 2.27, Taiwan 2.37, Taiwan 2.114, Merker México 6.31, and Mott), two tall elephantgrass cultivars (IRI 381 and Elephant B), and one interspecific hybrid (HV 241) of elephantgrass and pearl millet [ P. purpureum × P. glaucum (L.) R. Brown]. Adaptability and stability parameters were estimated for the following variables: herbage mass (HM), herbage accumulation rate (HAR), number of green leaves per tiller (NL/T), number of tillers (NT), and leaf/stem ratio. Interaction between clones and grazing periods occurred ( P ≤ 0.05) for all variables. Herbage mass ranged from 2180 kg dry matter (DM) ha −1 (Taiwan 2.37) to 3383 kg DM ha −1 (Mott), averaging 2796 kg DM ha −1 . Except for HV 241, which displayed specific adaptability to a favorable environment in HM and NT, the clones displayed wide adaptability. Dwarf genotypes (Taiwan 2.27, Taiwan 2.114, and Mott) displayed greater ( P ≤ 0.05) capacity of leaf production per tiller than the other entries. Mott and Taiwan 2.114 were selected for the next phase of the breeding program on the basis of stability, HAR, and NL/T.